The Effect of Telecommunication Services in Enhancing Economic Development in Banadir Region, Mogadishu, Somalia - Abdimalik Aden Ibrahim; Aweis Ahmed Hussein Jarras (SOTVI - Society of Visual Informatics, 2025)
This study investigates the impact of telecommunication services provided by Hormuud Telecom on economic development in the Banadir region of Mogadishu, Somalia. Employing a quantitative approach, this study examines how broadband Internet penetration, network coverage, and Internet usage influence key economic indicators, such as GDP growth, employment, and financial inclusion. Primary data were collected through closed-ended questionnaires administered to a sample of 100 participants, including Hormuud Telecom department leaders, employees, and customers. Secondary data on company and economic metrics were also utilized. The collected data were analyzed using descriptive Statistics and analysis performed in SPSS to explore the relationship between telecommunications development and economic growth. The findings reveal a strong positive perception of the impact of Hormuud Telecom's services on macroeconomic development, particularly in terms of rising GDP per capita and the proliferation of mobile money services such as EVC Plus. However, the study also uncovers a lack of consensus regarding the micro-economic benefits, with polarized views on the impact on local business growth, unemployment rates, and poverty reduction issues. Furthermore, the results highlight a significant gap between network coverage expansion and the quality and reliability of Internet services. The study concludes that while telecommunications infrastructure is a crucial enabler of economic development in the Banadir region, its full potential is moderated by factors such as service quality, digital literacy, and broader socioeconomic challenges. The findings offer valuable insights for policymakers, regulators, and industry stakeholders in Somalia, emphasizing the need for more inclusive and sustainable strategies to ensure that the benefits of digital growth are widely shared.